Protein profile of fiber types in human skeletal muscle: a single-fiber proteomics study - Marta Murgia (BMC, 2021)
Abstract Background Human skeletal muscle is composed of three major fiber types, referred to as type 1, 2A, and 2X fibers. This heterogeneous cellular composition complicates the interpretation of studies based on whole skeletal muscle lysate. A single-fiber proteomics approach is required to obtain a fiber-type resolved quantitative information on skeletal muscle pathophysiology. Methods Single fibers were dissected from vastus lateralis muscle biopsies of young adult males and processed for mass spectrometry-based single-fiber proteomics. We provide and analyze a resource dataset based on relatively pure fibers, containing at least 80% of either MYH7 (marker of slow type 1 fibers), MYH2 (marker of fast 2A fibers), or MYH1 (marker of fast 2X fibers). Results In a dataset of more than 3800 proteins detected by single-fiber proteomics, we selected 404 proteins showing a statistically significant difference among fiber types. We identified numerous type 1 or 2X fiber type–specific protein markers, defined as proteins present at 3-fold or higher levels in these compared to other fiber types. In contrast, we could detect only two 2A-specific protein markers in addition to MYH2. We observed three other major patterns: proteins showing a differential distribution according to the sequence 1 > 2A > 2X or 2X > 2A > 1 and type 2–specific proteins expressed in 2A and 2X fibers at levels 3 times greater than in type 1 fibers. In addition to precisely quantifying known fiber type–specific protein patterns, our study revealed several novel features of fiber type specificity, including the selective enrichment of components of the dystrophin and integrin complexes, as well as microtubular proteins, in type 2X fibers. The fiber type–specific distribution of some selected proteins revealed by proteomics was validated by immunofluorescence analyses with specific antibodies. Conclusion We here show that numerous muscle proteins, including proteins whose function is unknown, are selectively enriched in specific fiber types, pointing to potential implications in muscle pathophysiology. This reinforces the notion that single-fiber proteomics, together with recently developed approaches to single-cell proteomics, will be instrumental to explore and quantify muscle cell heterogeneity.